Femtomolar detection of phenol using surface-modified plasmonic refractive index sensor with sodium carboxymethyl cellulose - Hashim, Hazwani Suhaila; Fen, Yap Wing; Abdullah, Jaafar; Anuar, Muhammad Fahmi; Sheh Omar, Nur Alia; Liew, Josephine Ying Chyi; Mohd Daniyal, Wan Mohd Ebtisyam Mustaqim; Abdullah, Huda; Taufiq, Ahmad; Mahdi, Mohd Adzir (Elsevier, 2025)
The rapid expansion of industrial sectors to meet human demands has resulted in the widespread discharge of phenol, a key raw material, into the aquatic environments, posing serious threats to both ecosystems and human health due to its high toxicity and persistency. Although various techniques have been developed for phenol detection, many are costly, time-consuming, and difficult to implement. Surface plasmon resonance (SPR), a plasmonic refractive index sensor, has emerged as a valuable optical sensor to overcome these challenges. In this study, the SPR sensor was modified with sodium carboxymethyl cellulose (NaCMC) sensing layer for phenol detection. The sensor was evaluated over a phenol concentration range of 0.01–100 fM, exhibiting a rightward shift in the resonance angle with increasing concentrations. This shift is attributed to the binding of phenol to the NaCMC layer through hydrogen bonding, leading to the changes in the refractive index of the thin film. Optical analysis revealed an increase in the real part of the refractive index and film thickness, and a decrease in the imaginary part, when exposed to increasing phenol concentrations. Atomic force microscopy validated the interactions between NaCMC and phenol through distinct surface morphology and roughness changes. This sensor achieved an exceptionally low detection limit of 0.97 fM, the lowest one among the reported optical sensors, along with a sensitivity of 0.00895°/log10(fM). These findings highlight the outstanding sensitivity of the NaCMC-based SPR sensor for phenol detection and its strong potential for environmental monitoring.